Pollen Load and Flower Constancy of Three Species of Stingless Bees (Hymenoptera, Apidae, Meliponinae) - Norita Widya Pangestika; Tri Atmowidi; 2 Sih Kahono (Tropical Life Sciences Research, 2017)
The genus of stingless bees that play an important role as pollinators of plants. These bees are actively involved in the pollination of agricultural crops and known to have preferences in selecting flowers to pollinate. The aims of this study were to analyze the pollen load and flower constancy in Tetragonula laeviceps, Lepidotrigona terminata, and Heterotrigona itama. Each individual of species stingless bees collected and was put in a 1.5 ml micro-tube contain 0.5 ml 70% ethanol:glycerol (4:1). Pollen loads on each individual of stingless bees was counted by hemocytometer. Flower constancy of stingless bees was measured based on percentage of pollen type loaded on the body. Our results showed that the pollen loads of H. itama were the highest (31392 pollen grains) followed by L. terminata (23017 pollen grains) and T. laeviceps (8015 pollen grains). These species also demonstrated different flower constancy, with T. laeviceps on Poaceae flowers (76.49%), L. terminata on Euphorbiaceae flowers (80.46%), and H. itama on Solanaceae flowers (83.33%).